2021
DOI: 10.3389/fpsyg.2020.582480
|View full text |Cite
|
Sign up to set email alerts
|

Apriori Algorithm for the Data Mining of Global Cyberspace Security Issues for Human Participatory Based on Association Rules

Abstract: This study explored the global cyberspace security issues, with the purpose of breaking the stereotype of people’s cognition of cyberspace problems, which reflects the relationship between interdependence and association. Based on the Apriori algorithm in association rules, a total of 181 strong rules were mined from 40 target websites and 56,096 web pages were associated with global cyberspace security. Moreover, this study analyzed support, confidence, promotion, leverage, and reliability to achieve comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 39 publications
0
24
0
2
Order By: Relevance
“…The feature of this function is that it can complete any form of nonlinear mapping between the input layer and the output layer. Therefore, it endows the BPNN with absolute advantages in solving the problems of data classification, pattern recognition, and risk assessment [ 7 – 9 ].…”
Section: Bpnn and Evaluation Model Of Asset Qualitymentioning
confidence: 99%
“…The feature of this function is that it can complete any form of nonlinear mapping between the input layer and the output layer. Therefore, it endows the BPNN with absolute advantages in solving the problems of data classification, pattern recognition, and risk assessment [ 7 – 9 ].…”
Section: Bpnn and Evaluation Model Of Asset Qualitymentioning
confidence: 99%
“…They demonstrated that these four algorithms can effectively aid in the prevention of terrorist acts. Li, Li, Tang, and Zhang [8] used the Apriori algorithm to compare the frequency of phrases from global professional target websites to explore global cyber space security vulnerabilities. They demonstrated how the Apriori algorithm may be used to research and solve security issues in the global cyber domain.…”
Section: Related Workmentioning
confidence: 99%
“…The theory suggests that, when confronted with the specific social environment surrounding them, employees’ perceptions are triggered from these situational cues ( Zhu et al, 2019 ; Boudrias et al, 2021 ). Studies along this line found that one’s distinct subjective interpretations of various social cues can become a source of individual behaviors ( Brown et al, 2017 ; Zhu et al, 2019 ; Li et al, 2020 ). Meanwhile, according to regulatory focus theory, occupational stress factors can trigger the change of individual regulatory focus from progressive, explorative strategies to traditional, unadventurous strategies ( Brockner and Higgins, 2001 ; Brenninkmeijer and Hekkert-Koning, 2015 ; González-Cruz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%